2022
DOI: 10.3389/fimmu.2022.869741
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Mechanism of Action of TBBPA, TBBPS and Selected Bromophenols in Human Peripheral Blood Mononuclear Cells

Abstract: Bromophenolic flame retardants (BFRs) are a large group of synthetic substances used in the industry in order to reduce the flammability of synthetic materials used in electrical and electronic devices, textiles, furniture and other everyday products. The presence of BFRs has been documented in the environment, food, drinking water, inhaled dust and the human body. Due to the widespread exposure of the general population to BFRs and insufficient knowledge on their toxic action, including genotoxic potential, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
0
11
0
1
Order By: Relevance
“…An increase in reactive oxygen species (ROS) formation (as observed in our previous study on the prooxidative effects of 2,4,6-TBP and PBP on human PBMCs [34]) and raised cytosolic calcium ion level impair electrolyte transport across the mitochondrial membrane, causing the opening of the mitochondrial permeability transition pores (PTPs), which results in the release of various proapoptotic molecules, such as apoptosis-inducing factor (AIF), cytochrome c, and procaspase-9, into the cytosol [36]. As a consequence, an apoptosome is formed, which leads to caspase-9 activation, and subsequently to the initiation of the intrinsic (mitochondrial) pathway of apoptosis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…An increase in reactive oxygen species (ROS) formation (as observed in our previous study on the prooxidative effects of 2,4,6-TBP and PBP on human PBMCs [34]) and raised cytosolic calcium ion level impair electrolyte transport across the mitochondrial membrane, causing the opening of the mitochondrial permeability transition pores (PTPs), which results in the release of various proapoptotic molecules, such as apoptosis-inducing factor (AIF), cytochrome c, and procaspase-9, into the cytosol [36]. As a consequence, an apoptosome is formed, which leads to caspase-9 activation, and subsequently to the initiation of the intrinsic (mitochondrial) pathway of apoptosis.…”
Section: Discussionmentioning
confidence: 58%
“…In red blood cells, 2,4,6-TBP and PBP increased the level of reactive oxygen species (ROS), oxidized hemoglobin, and induced eryptosis [31][32][33]. Similarly, our previous research revealed that 2,4,6-TBP and PBP induced ROS formation, depleted ATP levels [34], and induced DNA strand breaks and DNA base oxidation in human peripheral blood mononuclear cells (PBMCs) [35]. It is known that ROS induction, the perturbation of energy production, and DNA damage are involved in apoptotic cell death [36].…”
Section: Introductionmentioning
confidence: 69%
“…In human peripheral blood mononuclear cells, a lower concentration of TBBPA induced DNA damage, stimulated oxidative mutilation to pyrimidines and purines [ 104 ]. A low TBBPA concentration was known to down-regulate the transmembrane transport of the cell membrane-related genes and cellular skeleton, proving that the membrane damage was genetically controlled.…”
Section: Mechanism Of Action Of Tbbpamentioning
confidence: 99%
“…18,19 However, adverse health effects on human beings need to be further investigated. Very recent studies on the carcinogenic nature of TCBPA and genotoxicity of TBBPA and TBBPS were elaborated by Lei et al 20 and Barańska et al, 21 respectively. TBBPA, TBBPS and TCBPA are known as common brominated flame retardants, and they are also often used in plastic paints, synthetic textiles, and electrical devices.…”
Section: Bisphenolsmentioning
confidence: 99%